Conventional coercion across the spectrum of operations : the utility of U. S. military forces in the emerging security environment - Johnson, David E. (David Eugene), 1950-; Mueller, Karl P.; Taft, William H., V.; Rand eBooks (Santa Monica, CA : RAND, 2002)
The raison d'étre for any military force is to deter an adversary from acting inimically to the nation's interests or, if the adversary is undeterred, to coerce him into ceasing, or in some cases reversing, the inimical actions. After carefully defining terms and reviewing the literature on coercion, this report delves into a study of the utility of military power as a coercive instrument of deterrence and compellence. The authors then analyze cases (both U.S. and foreign, successes and failures) that provide insights into conventional coercion at all levels of conflict. They conclude by stressing that the essential nature of coercion remains unchanged and that only a thorough understanding of the nation's adversaries, and of our own will and capabilities, will yield a successful coercive strategy.
Introduction -- The Theory of Coercion -- Case Study Results -- Implications and Insights -- Appendix: Case Studies.
"Arroyo Center."
Includes bibliographical references (p. 125-140).
Also available on the internet via WWW in PDF format.
Keywords: Deterrence (Strategy); World politics -- 21st century; United States -- Military policy; Electronic books